Blending Words Found In Social Media - Giyatmi Giyatmi; Ratih Wijayava; Sihindun Arumi (JURNAL ARBITRER, 2017)
There are many new words from the social media such as Netizen, Trentop, and Delcon. Those words include in blending. Blending is one of word formations combining two clipped words to form a brand new word. The researchers are interested in analyzing blend words used in the social media such as Instagram, Twitter, Facebook, and Blackberry Messenger. This research aims at (1) finding blend words used in the social media (2) describing kinds of blend words used in social media (3) describing the process of blend word formation used in the social media. This research uses some theories dealing with definition of blending and kinds of blending. This research belongs to descriptive qualitative research. Data of the research are English blend words used in social media. Data sources of this research are websites consisting of some English words used in social media and some social media users as the informant. Techniques of data collecting in this research are observation and simak catat. Observation is by observing some websites consisting of some English words used in social media. Simak catat is done by taking some notes on the data and encoding in symbols such as No/Blend words/Kinds of Blending. The researchers use source triangulation to check the data from the researchers with the informant and theory triangulation to determine kinds of blending and blend word formation in social media. There are115 data of blend words. Those data consists of 65 data of Instagram, 47 data of Twitter, 1 datum of Facebook, and 2 data of Blackberry Messenger. There are 2 types of blending used in social media;108 data of blending with clipping and 7 data of blending with overlapping. There are 10 ways of blend word formation found in this research.